A Health Twofer: Nurturing Relationships Are Associated with Lower Odds of Obesity-related Mental Health Comorbidities in Adolescence (P04-173-19). (13th June 2019) - Aguayo, Liliana; Lin, Annie; Davis, Matt M
Abstract: Objectives: This study proposes to identify dietary behaviors associated with two obesity-related mental health comorbidities (depression, and suicidal ideation), and examine whether a nurturing relationship with an adult at school can introduce protective effects against both comorbidities for adolescents. Methods: Students enrolled in 37 Chicago public high schools participated anonymously in the 2017 Youth Risk Behavior Survey. Students ( n = 1883) were asked about 1) dietary behaviors, such as if they ate fruits and/or vegetables at least once per week, drank milk and/or soda at least once per week, and ate breakfast daily and 2) mental health comorbidities, such as feeling sad or hopeless, or considered attempting suicide within the past year. There was an additional social support question that inquired whether there was at least one adult at the school that the student could consult with about an issue. Overweight or obesity (BMI P > 85th) were estimated using self-reported weight and height. Two sample-weighted logistic regression models, adjusted for physical activity, sleep, sex, age, race, and ethnicity, were used to examine factors associated with the co-occurrence of 1) overweight or obesity with depression, and 2) overweight or obesity with suicidal ideation. Results: Of the total sample, 13% had co-occurrence of depression with overweight or obesity and 7% were overweight or obese and experienced suicidal ideation. Having a nurturing relationship with an adult in school was associated with lower odds of obesity with comorbid depression (odds ratio (OR): 0.45; 95% confidence interval (CI):0.28–0.70) and lower odds of obesity with comorbid suicidal ideation (OR: 0.35; 95%CI: 0.23–0.52). Odds of obesity with comorbid depression were associated with soda (OR: 5.45; 95%CI: 3.76–7.90), and breakfast intake (OR: 0.32; 95%CI: 0.20–0.51). Odds of obesity with comorbid suicidal ideation were associated with milk (OR: 8.12; 95%CI: 4.77–13.83), and vegetable intake (OR: 3.38; 95%CI: 1.93–5.91), but no other dietary behavior. Conclusions: Further research is needed to examine the mechanisms through which nurturing relationships with adults at school introduced protective effects against the coexistence of obesity and mental health disorders for Chicago public high students. Funding Sources: Ms. Aguayo is supported by an American Heart Association Strategically Focused Research Network Award; Ms. Lin is supported by a NCI T32 Training Grant.